The association between body roundness index and risk of osteoporosis in patients with type 2 diabetes mellitus: A cross-sectional study based on NHANES database - Rensheng Chen; Wei Zhao; Pengfei Cai; Chao Peng; Hongxia Liu (Journal of Orthopaedic Surgery, 2025)
Background: Osteoporosis (OP) is a common complication in patients with type 2 diabetes mellitus (T2DM), significantly increasing fracture risk and mortality. Body roundness index (BRI), a novel obesity assessment index, accurately reflects body fat distribution, but its relationship with OP risk in T2DM patients has not been clarified. The aim of this study was to investigate the nonlinear relationship between BRI and OP risk in patients with T2DM. Methods: In this study, based on data from the 2005-2018 National Health and Nutrition Examination Survey, we conducted a cross-sectional study involving 3,178 people with T2DM. Femoral bone mineral density was measured using dual-energy X-ray absorptiometry. Generalized additive model was used to assess the non-linear relationship between BRI and OP risk. Multiple logistic regression analyses were used to assess the relationship between BRI and OP risk, adjusted for various covariates. Subgroup analyses for age, sex, and ethnicity were also performed to assess the consistency and robustness of the results. Results: Generalized additive model analyses demonstrated an L-shaped relationship between BRI and OP risk, and logistic regression analyses indicated that BRI exhibited a negative association with OP risk. The risk of OP exhibited a significant decrease with increasing BRI and appeared to saturate at a BRI of approximately 5.08. When the BRI was below 5.08, the risk of OP was reduced by 49% for each 1-unit increase (OR = 0.51, 95% CI: 0.37-0.71, p < .001); However, when the BRI exceeded 5.08, the protective effect diminished and became statistically non-significant (OR = 0.99, 95% CI: 0.88-1.11, p = .824). The log-likelihood ratio test demonstrated a significant model fit superiority ( p < .001). Subgroup analyses and interaction tests demonstrated that this association remained stable across various demographic and socioeconomic groups, including age, sex, education, poverty-to-income ratio, exercise, and smoking. However, race had an interaction association with BRI and OP risk ( p interaction < 0.050). Conclusion: Our study demonstrated that a negative association was found between BRI and OP risk in the United States population with T2DM and that this relationship was nonlinear. Further studies are needed to validate this.